2021
DOI: 10.21831/cp.v40i3.41758
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing prospective teachers’ creative thinking skills: A study of the transition from structured to open inquiry classes

Abstract: Creative thinking skills are considered to have a positive correlation with students’ academic achievement. Thus, they need to be developed through the learning process. To successfully develop these skills, an appropriate learning model is needed. This research aims to determine the improvement of the creative thinking skills of prospective teachers who learned using structured, guided, and open inquiries. This quasi-experimental research used an untreated control group design with pretest and posttest. A tot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…Other research using learning models or media that causes students to be active in their learning also shows similar results. For example, the application of the open inquiry model (Ramdani & Artayasa, 2020;Ramdani et al 2021), the Project Based Learning learning model (Sukarso et al 2019;Wijayati et al 2019), the application of augmented reality media (Faradillah & Maulida. 2022) can improve students' creative thinking skills.…”
Section: The Effect Of the It-srl Model In Improving Creative Thinkin...mentioning
confidence: 99%
“…Other research using learning models or media that causes students to be active in their learning also shows similar results. For example, the application of the open inquiry model (Ramdani & Artayasa, 2020;Ramdani et al 2021), the Project Based Learning learning model (Sukarso et al 2019;Wijayati et al 2019), the application of augmented reality media (Faradillah & Maulida. 2022) can improve students' creative thinking skills.…”
Section: The Effect Of the It-srl Model In Improving Creative Thinkin...mentioning
confidence: 99%
“…Based on the description above, it can be said that in lectures, learning material must be more focused on student learning needs. This is intended to make students have adequate insight into learning (Ramdani et al, 2021). The course material is determined based on the principle of meaningfulness for students as prospective teachers.…”
Section: The Students' Learning Needs In Bipa Lecturesmentioning
confidence: 99%
“…This research is pre-experimental using a one-shot case study design with a non-randomised control group pre-test and post-test model, as shown in Table 1 (Allen, 2017;Ramdani et al, 2021). Based on this design, each class is given a pre-test and post-test and application of the same Industrial Revolution 4.0-based TPACK model.…”
Section: Research Modelmentioning
confidence: 99%